Beyond Intuition: The Role of Financial Knowledge in Navigating Investments in Emerging Markets - Chowdhury, Nazreen Tabassum; Mahdzan, Nurul Shahnaz; Rahman, Mahfuzur (International Journal of Economics and Financial Issues, 2024)
Over the last century, global stock markets have crashed multiple times, leading to bankruptcy and unemployment and making individuals highly cautious about investing. Hence, individual investors in developing markets are highly prone to behavioural biases in their investment decisions, which influence their investment experience. The objective of this study is to examine the relationships between behavioural factors and investment experience, as well as the moderating effect of financial knowledge on individual investors in Bangladesh. Data was analysed using the partial least squares structural equation modelling (PLS-SEM) technique. The results revealed that behavioural factors such as anchoring, gambler’s fallacy, social interaction, and locus of control significantly influenced individual investors’ investment experiences. Moreover, financial knowledge had a moderating effect on these relationships. The study has important implications for investors, as it highlights the potential pitfalls of behavioural factors and the importance of financial knowledge in investors’ investment experience. The study’s findings imply that the government should develop new market opportunities through innovative products and take the necessary steps to incorporate regulations that will offer investors a better market experience.